Memahami Sistem Ekologi Sosial (SES) Dalam Konteks Kurikulum Merdeka Belajar - ArifLiputo, Muhammad (Jurusan Pendidikan IPS FKIP UNJA, 2023)
Abstract: The research aims to elaborate on the use of the â€œkurikulum merdeka belajarâ€ (Free learning curriculum) to provide learning about the Social Ecological System (SES) for students, enhancing their understanding of the importance of the between social, economic, and ecological aspects of living organisms in the environment. Social-ecological system are terms used in environmental science, ecology, and social science to describe the complex relationships between the social system (human) and the ecological system (Natural environment). This concept applies that humans cannot be separated from their natural environment, and both are interconnected in a complex system. The research employs a systematic literature review method. The literature used is derived from relevant sources that align with the topic. The findings indicate that knowledge about the balance of nature to support sustainability and the capacity of nature can be intensified in the â€œkurikulum merdeka belajarâ€ through teaching projects